Determination of Sodium Cromoglycate by a New Kinetic Spectrophotometric Method in Biological Samples - Mohsen Keyvanfard; Khadijeh Alizad; Razieh Shakeri (Journal of Chemistry)
A new kinetic spectrophotometric method is described for the determination of ultratrace amounts of sodium cromoglycate (SCG). The method based on catalytic action of SCG on the oxidation of amaranth with periodate in acidic and micellar medium. The reaction was monitored spectrophotometrically by measuring the decrease in absorbance of the amaranth at 518 nm, for the first 4 min from initiation of the reaction. Calibration curve was linear in the range of 4.0−36.0 ng mL−1 SCG. The limit of detection is 2.7 ng mL−1 SCG. The relative standard deviation (RSD) for ten replicate analyses of 12, 20, and 28 ng mL−1 SCG was 0.40%, 0.32%, and 0.53%, respectively. The proposed method was used for the determination of SCG in biological samples.